Pengaruh Promosi dan Electronic Word of Mouth terhadap Minat Berkunjung pada Sarlinda Cafe - Astria Juliarty; Almansyah Rundu Wonua; Niar Astaginy (Intellektika : Jurnal Ilmiah Mahasiswa, 2023)
This study aims to determine: (1) the effect of Promotion on Visiting Intensions at Sarlinda Cafe. (2) the effect Electronic Word of Mouth on Visiting Intensions at Sarlinda Cafe. This research is an Explanatory Research Model with a quantitative approach. Collecting data using observation, documentation, and questionnaires. The population in this study are people who have visited Sarlinda Cafe, which is 90 respondents using a purposive sampling technique, namely the technique of determining certain criteria. Testing research instruments using validity and reliability tests with SPSS 25.0. The data analysis technique used in this study is structural equation modeling (SEM) based on Partial least Squares (PLS) using the Smart-PLS 4.0 application. Based on the results of the study it is known that there is positive and significant influence between the Promotion variables on Visiting Intensions, as well as the Electronic Word of Mouth variable which has a positive and significant influence on Visiting Intensions.